Jovens, escola e mundo do trabalho: experiências e significados em São Miguel Arcanjo- SP. - Demarchi, Rodrigo Geraldi (Universidade Federal de São Carlos, 2018)
The research analyzed the experiences and trajectories of schooling and work, together with the meanings attributed to these spheres by young men and women who finished high school in the municipality of São Miguel Arcanjo - São Paulo, a place marked by strong traits of rurality. From the theoretical point of view, reference was made to studies on youth, especially on rural youth and on the current flows between the urban and the rural in contemporary times, increasingly present in places that could once be called exclusively rural (José Machado Pais, Vanda Silva, Elisa Guaraná Castro, Maria José Carneiro). The research is qualitative, using the technique of semi-structured interviews conducted with six boys and eight girls between 17 and 21 years old, who finished high school between the years 2015 and 2017. The analysis of the data revealed in a forceful way the presence of school and work in the lives of these young people, as well as a strong interweaving with the characteristics of "rurbanidade" identified between them and the community where they are inserted. At the same time, the presence of flows and transits (between the rural and urban areas and between the locality of São Miguel and other urban centers) experienced by these and these young people associated with strategies of continuity of studies, expansion of the options economic assistance to the family group (through pluriactivity) and the desire to know and live in places other than those of their origin.
Jóvenes, escuela y mundo del trabajo: experiencias y significados en São Miguel Arcanjo- SP.
Keywords: Juventude; Juventud; Youth; Juventude rural; Escola; Trabalho; Trajetórias; Juventud rural; Escuela; Escuela; Trabajo; Trayectorias; Rural youth; School; Job; Trajectories; CIENCIAS HUMANAS::EDUCACAO